Crosslinked acrylate copolymer as well as preparation method and application thereof

By introducing furan instead of acrylate and coupling agent in the acrylate rubber synthesis process, and using Diels-Alder reaction to form a reversible crosslinking network structure, the problem of low recycling efficiency of acrylate rubber in the prior art is solved, and the repetitive processing and performance improvement of the material is achieved.

CN119912643AActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311434576.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

Existing acrylate rubbers are very inefficient during recycling, and vulcanized crosslinking technology makes the material unprocessable.

Method used

By introducing furan-substituted acrylate and coupling agent in the acrylate rubber synthesis process, a reversible crosslinking network structure is formed using the Diels-Alder reaction to achieve repeatable processing of the material.

Benefits of technology

Reversible decrosslinking of crosslinked acrylate rubber is realized, which gives the material a repeating processability, and improves the strength, deformation resistance and elasticity of the material, which is of great environmental significance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912643A_ABST
    Figure CN119912643A_ABST
Patent Text Reader

Abstract

The invention relates to the field of rubber materials, and discloses a cross-linked acrylate copolymer and a preparation method and application thereof.The copolymer comprises a structural unit A from acrylate, a structural unit B from ethylene, a structural unit C from furan-substituted acrylate and a structural unit D from a coupling agent, and based on the total amount of the copolymer, the structural unit A and the structural unit B are selected from the group consisting of acrylic acid, ethylene and furan-substituted acrylate; the content of the structural unit A is 10-80wt%, the content of the structural unit B is 15-82wt%, the content of the structural unit C is 3-10wt%, and the content of the structural unit D is 1-6wt%. The acrylate copolymer disclosed by the invention is a material with a reversible cross-linked network structure, and the network structure is formed in the prepared acrylate copolymer by adding the coupling agent; the cross-linking strengthening of the rubber is realized; by utilizing the thermal reversibility of the D-A reaction, when the copolymer is heated to 120 DEG C or above, the decrosslinking of the rubber can be realized, so that the rubber has hot workability; when the temperature is reduced to 80 DEG C or below, crosslinking can be performed again to generate a network structure, so that the mechanical property of the rubber is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of rubber materials, and in particular to a cross-linked acrylate copolymer and a preparation method and application thereof. Background Art

[0002] Acrylic rubber is widely used in the automotive industry due to its outstanding high-temperature oil resistance and high-temperature anti-aging properties. The introduction of ethylene into acrylic polymers can improve the cold resistance of the material and further broaden the scope of use of acrylic rubber. However, uncrosslinked acrylic rubber does not have the elasticity, resilience, strength and dimensional stability required in the rubber application process, so crosslinking modification is necessary.

[0003] Vulcanization cross-linking is the main cross-linking technology for polymer materials at present. The cross-linking covalent bonds formed by it are irreversible, making it impossible to reprocess the cross-linked polymer. Therefore, while giving the material excellent properties, it also brings about the problem of recycling and reuse of polymer materials. People usually use a combination of heat treatment and mechanical treatment to destroy the vulcanization cross-linking bonds, but this process will cause the main chain of the polymer to break, and only 25% of the product obtained after desulfurization can be reused.

[0004] In recent years, with the increase of human environmental awareness, many countries and regions have developed rubber recycling and reuse into a real industry. Recycled waste can not only be converted into new energy or other materials, but also bring considerable economic benefits. Realizing the green recycling of cross-linked rubber and avoiding material damage caused by the processing process as much as possible so that it can be recycled is a common goal pursued by researchers and the industry.

[0005] If the construction of reversible cross-linking structure can be achieved during the synthesis process of acrylic rubber, and cross-linked acrylic rubber with reproducible processability can be prepared directly in the polymerization reactor, it will not only be possible to innovate the synthesis method, but also achieve innovation in product performance and have important environmental significance. Summary of the invention

[0006] The purpose of the present invention is to overcome the problem of very low recycling efficiency of existing acrylic rubber in the prior art, and to provide a cross-linked acrylic copolymer and its preparation method and application. The cross-linked acrylic copolymer can be dissociated by reverse reaction at high temperature, so that the cross-linked acrylic copolymer is de-crosslinked, giving the cross-linked polymer repeatability, thereby facilitating recycling and reuse.

[0007] In order to achieve the above object, the first aspect of the present invention provides a cross-linked acrylate copolymer, wherein the copolymer comprises a structural unit A derived from acrylate, a structural unit B derived from ethylene, a structural unit C derived from furan-substituted acrylate, and a structural unit D derived from a coupling agent;

[0008] Based on the total amount of the copolymer, the content of the structural unit A is 10-80 wt %, the content of the structural unit B is 15-82 wt %, the content of the structural unit C is 3-10 wt %, and the content of the structural unit D is 1-6 wt %.

[0009] The second aspect of the present invention provides a method for preparing a cross-linked acrylate copolymer, wherein acrylate, furan-substituted acrylate and ethylene are polymerized in the presence of an initiator, and after the reaction, the ethylene is discharged and a coupling agent is added to carry out a cross-linking reaction to obtain a cross-linked acrylate copolymer.

[0010] A third aspect of the present invention provides a use of a cross-linked acrylate copolymer as a reinforced acrylate rubber material.

[0011] Dynamic covalent chemistry provides a very effective method for preparing polymers with reversible structural changes. Dynamic covalent reaction is a reversible chemical process between molecules through the formation and breaking of covalent bonds. Common dynamic covalent reactions used in polymer synthesis include Diels-Alder (DA) reaction, disulfide bond, imine bond, acylhydrazone bond, reversible boronate esterification reaction, reversible free radical reaction, etc., which can undergo reversible structural changes between reactants and products under specific stimulation conditions (heat, pH, light, redox reagents, etc.). DA reaction (Diels-Alder reaction) is an effective cycloaddition reaction. It forms a stable six-membered ring compound through a [4+2] cycloaddition reaction between an electron-rich diene and an electron-deficient dienophile. The reaction does not require a catalyst and is easy to implement.

[0012] The reaction process of the present invention is as follows Figure 3 and 4 First, acrylate, ethylene, and furan are substituted for acrylate to undergo polymerization reaction to obtain ethylene-acrylate rubber having a furan group on the side group, such as Figure 3 As shown; the ethylene-acrylate rubber with furan groups on the side groups is cross-linked with a coupling agent, and the maleimide groups at both ends of the coupling agent react with the furan groups on the side groups of the ethylene-acrylate rubber to form a cross-linked network structure between different ethylene-acrylate rubber molecular chains to obtain a cross-linked acrylate copolymer. The mechanism is as follows: Figure 4 As shown, the main chains of the obtained copolymer are cross-linked through bridge chains, and the bridge chains include furan groups from furan-substituted furfuryl acrylate and maleimide groups from the coupling agent.

[0013] Determination of the cross-linked acrylate copolymer obtained 1 H-NMR spectrum, the results are as follows Figure 1As shown in the figure, the chemical shift at 5.1 ppm is the characteristic peak of the hydrogen atom in -OCH2- connected to the furan group in furan-substituted furfuryl acrylate, and the chemical shift at 6.4 ppm and 7.5 ppm are the characteristic peaks of the hydrogen atom on the furan ring in furan-substituted furfuryl acrylate, respectively, which proves that the furan group is successfully introduced on the side group of ethylene-acrylate rubber.

[0014] The cross-linked acrylate copolymer obtained was observed by infrared spectroscopy. It was found that the in-plane bending vibration of the ether bond COC in the six-membered ring produced by the DA reaction appeared at 1177 cm -1 The temperature-dependent FTIR test was used to observe the formation and breaking process of DA bonds in cross-linked acrylate copolymers as the temperature changes. The cross-linked sample was heated to 140°C for infrared data scanning, and the 1177 cm -1 The intensity of the characteristic peak of DA bond at 1177cm -1 The characteristic intensity of the DA bond at increases again, indicating that the DA reaction occurs. This indicates that the reversible process of DA reaction dissociation at increasing temperature and association at decreasing temperature is successfully realized in the synthesized acrylic rubber prepared by the present invention.

[0015] The acrylate copolymer of the present invention is a material with a reversible cross-linked network structure. A coupling agent is added to form a network structure in the prepared acrylate copolymer to achieve cross-linking and strengthening of the rubber. The thermal reversibility of the DA reaction is utilized to heat the copolymer to above 120°C to achieve decrosslinking of the rubber, so that the rubber has heat processability. When the copolymer is cooled to below 80°C, it can be cross-linked again to generate a network structure, so that the mechanical properties of the rubber are enhanced.

[0016] The prepared acrylic copolymer is used as a reinforced acrylic rubber, and has excellent properties such as high strength, excellent deformation resistance, good elasticity, and repeatable processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The cross-linked acrylate copolymers obtained in Example 2 and Comparative Example 1 are 1 H-NMR spectrum;

[0018] Figure 2 is the infrared spectrum of the cross-linked acrylate copolymer obtained in Example 2 of the present invention;

[0019] Figure 3 It is a reaction mechanism diagram of the polymerization reaction in the present invention;

[0020] Figure 4 Schematic diagram of the reaction mechanism of the cross-linking reaction in the present invention. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] The first aspect of the present invention provides a cross-linked acrylate copolymer, wherein the copolymer comprises a structural unit A derived from acrylate, a structural unit B derived from ethylene, a structural unit C derived from furan-substituted acrylate, and a structural unit D derived from a coupling agent;

[0023] Based on the total amount of the copolymer, the content of the structural unit A is 10-80 wt %, the content of the structural unit B is 15-82 wt %, the content of the structural unit C is 3-10 wt %, and the content of the structural unit D is 1-6 wt %.

[0024] In the present invention, the carbon-carbon double bonds contained in acrylate, ethylene and furan-substituted acrylate are subjected to addition polymerization to form multiple copolymer chains, and the coupling agent reacts with the furan group contained in the side group of the structural unit C in different copolymer chains through the double terminal group it has through DA reaction to form a six-membered ring structure containing a bridged ether bond, thereby achieving cross-linking connection between different copolymer chains, that is, the coupling agent provides a connection structure or connection group between different copolymer chains.

[0025] In some embodiments of the present invention, preferably, the gel content of the copolymer is not less than 80%, and the infrared spectrum of the copolymer is at 1177cm -1 The characteristic peak of ether bond COC appears nearby. The DA reaction forms a six-membered ring. The appearance of the characteristic peak of COC bond in the six-membered ring indicates that the DA reaction is successfully introduced into the obtained copolymer, so that it has the performance of decrosslinking at high temperature and repolymerization at low temperature.

[0026] The gel content of the copolymer is not less than 80wt%. By measuring the gel content, it can be determined whether the polymer is cross-linked and the efficiency of the cross-linking. The acrylate monomer is selected from at least one of methyl acrylate, ethyl acrylate, and butyl acrylate. Based on the total amount of the copolymer, the content of the structural unit A can be any value within a numerical range consisting of any two of 10wt%, 15wt%, 25wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, and 80wt%. The content of the structural unit B can be 15wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, and 80wt%. The content of the structural unit C can be any value within the numerical range composed of any two numbers among 40wt%, 50wt%, 60wt%, 70wt%, 75wt%, 82wt%; the content of the structural unit C can be any value within the numerical range composed of any two numbers among 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%; the content of the structural unit D can be any value within the numerical range composed of any two numbers among 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%.

[0027] In some embodiments of the present invention, preferably, the elongation at break of the copolymer is not less than 180%. The elongation at break reflects the elasticity and toughness of the polymer, and the elongation at break of the polymer is not less than 180%, preferably not less than 240%.

[0028] In some embodiments of the present invention, preferably, the furan-substituted acrylate is selected from and / or Preferably The methyl-free furan-substituted acrylate can make the prepared polymer have a lower glass transition temperature, thereby making it more resistant to low temperatures.

[0029] In some embodiments of the present invention, preferably, the coupling agent is selected from and / or Wherein R is an alkyl group of 1 to 10 carbon atoms. R can be an alkylene group of 1, 5 or 10 carbon atoms.

[0030] The second aspect of the present invention provides a method for preparing a cross-linked acrylate copolymer, wherein acrylate, furan-substituted acrylate and ethylene are polymerized in the presence of an initiator, ethylene is discharged after the reaction, and a coupling agent is added to carry out a cross-linking reaction to obtain a cross-linked acrylate copolymer.

[0031] In the present invention, acrylate, furan-substituted acrylate and ethylene are used as monomers, and the carbon-carbon double bonds contained in each monomer undergo addition polymerization to form a polymer chain; then the terminal maleimide group contained in the coupling agent reacts with the furan group introduced into the polymer chain by the furan-substituted acrylate monomer to form a connection structure between different polymer chains to form a cross-linked acrylate copolymer. The schematic diagram of the above reaction mechanism is shown in FIG. Figure 3 and 4 As shown in the example.

[0032] In some embodiments of the present invention, preferably, the mass ratio of the furan substituted acrylate to the acrylate is 1:9-3:8. The mass ratio of the furan substituted acrylate to the acrylate can be any value within the numerical range consisting of any two numbers of 1:9, 3:17, 4:17, and 3:8.

[0033] In some embodiments of the present invention, preferably, the pressure of the ethylene monomer is 1-100 MPa.

[0034] The amount of acrylate and ethylene affects the glass transition temperature and crosslinking efficiency of the polymer, wherein the crosslinking efficiency is reflected by the gel content. The molar ratio of furan substituted acrylate to the acrylate can be any value within the numerical range of any two numbers consisting of 0.01:1, 0.05:1, 0.1:1, 0.3:1, and 0.5:1; the ethylene pressure can be any value within the numerical range of any two numbers consisting of 1MPa, 10MPa, 20MPa, 30MPa, 50MPa, and 100MPa.

[0035] In some embodiments of the present invention, preferably, the amount of the initiator is 0.01-1wt% of the total mass of the acrylate and furan-substituted acrylate. The initiator can be one or more of a thermal decomposition free radical initiator, an organic peroxide, and an azo initiator, preferably an alkyl peroxide, a hydroperoxide, an acyl peroxide, and a peroxycarbonate. The alkyl peroxide can be specifically triethylaluminum; triethylboron; triethyllead; the hydroperoxide can be specifically cumene hydroperoxide and tert-butyl hydroperoxide; the acyl peroxide can be specifically benzoyl peroxide and lauroyl peroxide; the peroxycarbonate can be specifically diisopropyl peroxydicarbonate and dicyclohexyl peroxydicarbonate; the azo initiator can be specifically azobisisobutyronitrile and azobisisoheptonitrile. The amount of the initiator is any value within the numerical range consisting of any two of 0.01wt%, 0.05wt%, 0.1wt%, 0.5wt%, and 1wt% of the total mass of the acrylate and furan-substituted acrylate.

[0036] In some embodiments of the present invention, preferably, the polymerization temperature is 0-100°C and the time is 0.1-12h. Too high or too low polymerization temperature will lead to a small ethylene insertion rate and poor thermal properties of the polymer; short reaction time, low polymer molecular weight, poor thermal properties, long reaction time, too large molecular weight, and unfavorable processing. The polymerization temperature can be any value within the numerical range of any two numbers of 0°C, 20°C, 50°C, 80°C, and 100°C.

[0037] In some embodiments of the present invention, preferably, a solvent is further included, and before the polymerization reaction, the acrylate and furan-substituted acrylate are mixed with the solvent. The solvent is an alkane with 5 to 10 carbon atoms and / or an aromatic hydrocarbon with 6 to 10 carbon atoms, wherein the alkane with 5 to 10 carbon atoms is selected from at least one of n-pentane, n-hexane, cyclohexane, n-heptane, n-octane, and n-decane; the aromatic hydrocarbon with 6 to 10 carbon atoms is selected from at least one of benzene, toluene, xylene, ethylbenzene, n-propylbenzene, and isopropylbenzene. The mass ratio of the total mass of the acrylate and furan-substituted acrylate to the solvent can be any value within the numerical range consisting of any two numbers of 1:100, 300:100, 500:100, 800:100, and 1000:100.

[0038] In some embodiments of the present invention, preferably, the mass ratio of the coupling agent to the furan-substituted acrylate is 0.1-0.5:1. The coupling agent and the furan-substituted acrylate together give the polymer a reversible crosslinking function. There are two ways to add the coupling agent: ① directly add it to the reaction system; ② disperse the coupling agent in an organic solvent and then add it to the reaction system. The organic solvent in method ② can be the same as or different from the solvent used in the polymerization reaction, and can be selected from at least one of n-pentane, n-hexane, cyclohexane, n-heptane, n-octane, and n-decane, or selected from at least one of benzene, toluene, xylene, ethylbenzene, n-propylbenzene, and isopropylbenzene.

[0039] In some embodiments of the present invention, preferably, the temperature of the cross-linking reaction is 40-80°C and the time is 0.1-12h. If the cross-linking reaction temperature is too low, the obtained polymer has low molecular weight and poor mechanical properties. If the reaction temperature is high, gel is easily produced. If the reaction time is short, the molecular weight of the polymer is low and the mechanical properties are poor. If the reaction time is long, the molecular weight is too large and gel is produced, which is not conducive to processing. Therefore, the cross-linking reaction temperature can be any value within the numerical range composed of any two numbers of 40°C, 60°C, and 80°C, and the cross-linking time is any value within the numerical range composed of any two numbers of 0.1h, 3h, 6h, 9h, and 12h.

[0040] The third aspect of the present invention provides an application of a cross-linked acrylic ester copolymer as a reinforced acrylic ester rubber material. Compared with an uncross-linked copolymer, the tensile strength of the copolymer prepared by the present invention is significantly increased. Compared with the conventional vulcanization cross-linking, the tensile strengths of the two are equivalent, but the copolymer of the present invention has a greater elongation at break, that is, has better elasticity and toughness.

[0041] According to a particularly preferred embodiment of the present invention, based on the total amount of the copolymer, the content of the structural unit A is 10-60wt%, the content of the structural unit B is 30-82wt%, the content of the structural unit C is 6-8wt%, and the content of the structural unit D is 2-3wt%.

[0042] The present invention will be described in detail below through examples. In the following examples, the gel content is measured by the DMF room temperature swelling method; the glass transition temperature is measured by the DSC method; the tensile strength and elongation at break are measured according to GB / T 1040.1-2006.

[0043] Coupling agent D: N,N'-(4,4'-methylenediphenyl)bismaleimide, purchased from Anaiji Chemical, CAS No. 13676-54-5, structural formula:

[0044] Methyl acrylate was purchased from Alfa Company;

[0045] Ethyl acrylate was purchased from Alfa Company;

[0046] Butyl acrylate was purchased from Alfa Company;

[0047] Ethylene was purchased commercially from Searle Gas Company;

[0048] Azobisisobutyronitrile was purchased from Aladdin.

[0049] Preparation Example 1

[0050] Synthesis of Furfuryl Acrylate (A):

[0051] 10.85g of furfuryl alcohol and 16.58g of triethylamine were poured into a flask filled with 100mL of dichloromethane, and stirred in an ice-water bath for 10min; then 10.14g of acryloyl chloride was injected into a dropping funnel through a syringe after nitrogen replacement three times, and slowly dripped into the flask after sealing (about 30min to complete the dripping), and after continuous stirring in an ice-water bath for 5h, the product was filtered, and the filtrate was extracted with a saturated NaCl aqueous solution, a saturated NaHCO3 aqueous solution, and a saturated NaCl aqueous solution in sequence, and the organic phase was collected, dried over anhydrous magnesium sulfate, and filtered. The filtrate was distilled under reduced pressure to remove the solvent dichloromethane to obtain furfuryl acrylate A:

[0052] Preparation Example 2

[0053] Synthesis of Furfuryl Methacrylate (B):

[0054] 11.77g of furfuryl alcohol and 18.24g of triethylamine were poured into a flask filled with 100mL of dichloromethane, and stirred in an ice-water bath for 10min; then 18.72g of methacryloyl chloride was injected into a dropping funnel through a syringe after nitrogen replacement three times, and slowly dripped into the flask after sealing (about 30min to drip), and after continuous stirring in an ice-water bath for 5h, the product was filtered, and the filtrate was extracted with a saturated NaCl aqueous solution, a saturated NaHCO3 aqueous solution, and a saturated NaCl aqueous solution in sequence, and the organic phase was collected, dried with anhydrous magnesium sulfate, and filtered. The filtrate was distilled under reduced pressure to remove the solvent dichloromethane to obtain furfuryl methacrylate B:

[0055] Preparation Example 3

[0056] Synthesis of 1,6-dimaleimidohexane (C):

[0057] Dissolve furan protected maleic anhydride (60.2mmol) and triethylamine (7mL) in 60mL methanol, then drop hexamethylenediamine (25.1mmol) in methanol in an ice-water bath, and then reflux the resulting mixed solution in an 80°C oil bath for 48h under nitrogen. After reflux, place the solution in a -20°C refrigerator to obtain pale yellow crystals, which are pumped to dryness with a vacuum pump, then dissolved in 50mL toluene, and refluxed in an oil bath at 120°C for 48h under nitrogen. After reflux, place the solution in a -20°C refrigerator again to obtain pale yellow crystals, which are pumped to dryness with a vacuum pump to obtain coupling agent C:

[0058] Example 1

[0059] In a 2L reactor, add 200mL toluene, 45g methyl acrylate, 5g furfuryl acrylate A, 0.2g azobisisobutyronitrile as initiator, introduce 10MPa ethylene gas, and react at 70℃ for 3h. After the reaction, ethylene in the reactor is vented, 10mL of n-hexane solution dispersed with 2.5g coupling agent C is added to the reactor, and reacted at 70℃ for 3h. Collect the product, wash and dry to obtain 74g of product. The polymer composition is shown in Table 1, and the basic properties are shown in Table 2.

[0060] Example 2

[0061] In a 2L reactor, add 200mL toluene, 45g methyl acrylate, 40g ethyl acrylate, 15g furfuryl acrylate A, 0.5g azobisisobutyronitrile initiator, introduce 10MPa ethylene gas, and react at 70℃ for 3h. After the reaction, ethylene in the reactor is vented, 10mL of n-hexane solution dispersed with 4g coupling agent C is added to the reactor, and reacted at 70℃ for 3h. Collect the product, wash and dry to obtain 155g of product. The polymer composition is shown in Table 1, and the basic properties are shown in Table 2.

[0062] The prepared copolymers were measured using a Varian DLG 400 nuclear magnetic resonance spectrometer with deuterated tetrachloroethane as solvent at 100 °C. 1 H-NMR spectra, such as Figure 1 As shown. The peaks between the chemical shift of 1.0-2.5ppm are characteristic peaks of hydrogen atoms in the polymer main chain and hydrogen atoms from -CH3 in ethyl acrylate, and the peak at the chemical shift of 4.2ppm is the characteristic peak of -OCH2- hydrogen atoms in ethyl acrylate. Compared with the polymer without furfuryl acrylate (Comparative Example 1), it can be clearly seen that in the copolymer prepared in Example 2, the newly appeared chemical shift at 5.1ppm is the characteristic peak of hydrogen atoms in -OCH2- connected to the furan group in furfuryl acrylate A, and the characteristic peaks at 6.4ppm and 7.5ppm are respectively the characteristic peaks of hydrogen atoms on the furan ring in furfuryl acrylate A, proving that the furan group was successfully introduced into the side group of ethylene-acrylate rubber.

[0063] The prepared polymer was further pressed and molded on a flat plate vulcanizer at 180° C., cut into small pieces, and then pressed and molded on a flat plate vulcanizer again at 180° C. to obtain Example 2′. The properties of the tested polymer are shown in Table 2.

[0064] The polymer obtained in Experimental Example 2' was further cut into small pieces, and again placed on a flat plate vulcanizer at 180° C. to form Example 2'. The test performance results are shown in Table 2.

[0065] Example 3

[0066] In a 2L reactor, add 200mL toluene, 45g methyl acrylate, 35g butyl acrylate, 15g furfuryl methacrylate B, 0.2g azobisisobutyronitrile as initiator, introduce 10MPa ethylene gas, and react at 70℃ for 3h. After the reaction, ethylene in the reactor is vented, 10mL of n-hexane solution dispersed with 3.0g coupling agent C is added to the reactor, and reacted at 70℃ for 3h. Collect the product, wash and dry to obtain 140g of product. The polymer composition is shown in Table 1, and the basic properties are shown in Table 2.

[0067] Example 4

[0068] In a 2L reactor, add 200mL of n-heptane, 45g of methyl acrylate, 40g of ethyl acrylate, 15g of furfuryl acrylate A, 0.2g of initiator azobisisobutyronitrile, introduce 30MPa of ethylene gas, and react at 70℃ for 3h. After the reaction, ethylene in the reactor is vented, 10mL of n-hexane solution dispersed with 4.0g of coupling agent C is added to the reactor, and reacted at 70℃ for 3h. Collect the product, wash and dry to obtain 195g of product. The polymer composition is shown in Table 1, and the basic properties are shown in Table 2.

[0069] Example 5

[0070] In a 2L reactor, add 200mL of n-heptane, 45g of methyl acrylate, 40g of ethyl acrylate, 15g of furfuryl acrylate A, 0.2g of initiator azobisisobutyronitrile, introduce 30MPa of ethylene gas, and react at 70℃ for 3h. After the reaction, ethylene in the reactor is vented, 10mL of n-hexane solution dispersed with 5g of coupling agent D is added to the reactor, and reacted at 70℃ for 3h. Collect the product, wash and dry to obtain 196g of product. The polymer composition is shown in Table 1, and the basic properties are shown in Table 2.

[0071] Example 6

[0072] In a 2L reactor, add 200mL toluene, 40g ethyl acrylate, 15g furfuryl methacrylate B, 0.2g azobisisobutyronitrile as initiator, introduce ethylene gas at 20MPa, and react at 70℃ for 3h. After the reaction, ethylene in the reactor is vented, 10mL of n-hexane solution dispersed with 2g coupling agent D is added to the reactor, and reacted at 70℃ for 5h. Collect the product, wash and dry to obtain 122g of product. The polymer composition is shown in Table 1, and the basic properties are shown in Table 2.

[0073] Example 7

[0074] In a 2L reactor, add 200mL of n-heptane, 45g of methyl acrylate, 40g of ethyl acrylate, 20g of furfuryl acrylate A, 0.5g of initiator azobisisobutyronitrile, introduce 10MPa of ethylene gas, and react at 70℃ for 4h. After the reaction, ethylene in the reactor is vented, 10mL of n-hexane solution dispersed with 8.0g of coupling agent C is added to the reactor, and reacted at 70℃ for 4h. Collect the product, wash and dry to obtain 170g of product. The polymer composition is shown in Table 1, and the basic properties are shown in Table 2.

[0075] Example 8

[0076] In a 2L reactor, add 200mL toluene, 45g methyl acrylate, 40g ethyl acrylate, 10g furfuryl acrylate A, 5g furfuryl methacrylate B, 0.5g azobisisobutyronitrile initiator, introduce 10MPa ethylene gas, and react at 70℃ for 4h. After the reaction, ethylene in the reactor is vented, 10mL of n-hexane solution dispersed with 2.0g coupling agent C and 2.0g coupling agent D is added to the reactor, and reacted at 70℃ for 3h. Collect the product, wash and dry to obtain 155g of product. The polymer composition is shown in Table 1, and the basic properties are shown in Table 2.

[0077] Example 9

[0078] In a 2L reactor, add 200mL toluene, 45g methyl acrylate, 40g ethyl acrylate, 15g furfuryl acrylate A, 0.01g azobisisobutyronitrile as initiator, introduce 1MPa ethylene gas, and react at 0℃ for 0.1h. After the reaction, ethylene in the reactor is vented, 10mL of n-hexane solution containing 4g coupling agent C is added to the reactor, and the reaction is carried out at 40℃ for 0.1h. The product is collected, washed and dried. The composition of the obtained polymer is shown in Table 1, and the basic properties are shown in Table 2.

[0079] Example 10

[0080] In a 2L reactor, add 200mL toluene, 45g methyl acrylate, 40g ethyl acrylate, 15g furfuryl acrylate A, 0.5g azobisisobutyronitrile initiator, introduce ethylene gas at 50MPa, and react at 50℃ for 6h. After the reaction, ethylene in the reactor is vented, 10mL of n-hexane solution dispersed with 4g coupling agent C is added to the reactor, and reacted at 60℃ for 5h. Collect the product, wash and dry it, and the obtained polymer composition is shown in Table 1, and the basic properties are shown in Table 2.

[0081] Embodiment 11

[0082] In a 2L reactor, add 200mL toluene, 45g methyl acrylate, 40g ethyl acrylate, 15g furfuryl acrylate A, 1g azobisisobutyronitrile initiator, introduce 100MPa ethylene gas, and react at 100℃ for 12h. After the reaction, ethylene in the reactor is vented, 10mL of n-hexane solution dispersed with 4g coupling agent C is added to the reactor, and reacted at 80℃ for 12h. Collect the product, wash and dry it, and the obtained polymer composition is shown in Table 1, and the basic properties are shown in Table 2.

[0083] Comparative Example 1

[0084] In a 2L reactor, add 200mL toluene, 45g methyl acrylate, 40g ethyl acrylate, add 0.5g azobisisobutyronitrile as initiator, introduce 10MPa ethylene gas, and react at 70℃ for 3h. After the reaction, collect the product, wash and dry to obtain 150g of the product. The polymer composition is shown in Table 1, and the basic properties are shown in Table 2.

[0085] Comparative Example 2

[0086] In a 2L reactor, add 200mL toluene, 45g methyl acrylate, 40g ethyl acrylate, 15g furfuryl acrylate A, 0.5g azobisisobutyronitrile as initiator, introduce 10MPa ethylene gas, and react at 70℃ for 3h. After the reaction, collect the product, wash and dry to obtain 151g of the product. The polymer composition is shown in Table 1, and the basic properties are shown in Table 2.

[0087] Comparative Example 3

[0088] In a 2L reactor, add 200mL toluene, 45g methyl acrylate, 40g ethyl acrylate, 0.5g azobisisobutyronitrile as initiator, introduce 10MPa ethylene gas, and react at 70℃ for 3h. After the reaction, ethylene in the reactor is vented, 10mL of n-hexane solution dispersed with 4.0g coupling agent C is added to the reactor, and reacted at 70℃ for 3h. Collect the product, wash and dry to obtain 165g of product. The polymer composition is shown in Table 1, and the basic properties are shown in Table 2.

[0089] Comparative Example 4

[0090] In a 2L reactor, add 200mL toluene, 45g methyl acrylate, 40g ethyl acrylate, 15g acrylic acid, 0.5g azobisisobutyronitrile as initiator, introduce 10MPa ethylene gas, and react at 70℃ for 3h. After the reaction, collect the product, wash and dry to obtain 162g of the product. After conventional vulcanization and crosslinking, the mechanical properties are tested. The polymer composition is shown in Table 1, and the basic properties are shown in Table 2.

[0091] Table 1

[0092]

[0093]

[0094] Table 2

[0095]

[0096]

[0097] The cross-linked acrylate copolymer prepared by the method of the present invention has a cross-linked network structure formed by reversible chemical bonds. The cross-linked network formed in the material can be verified by gel test. The tensile strength of the material is significantly higher than that of the samples of Comparative Examples 1-3 without a cross-linked network structure. For example, by comparing Example 2 with Comparative Examples 1-3, it can be seen that the gel content of the cross-linked acrylate copolymer prepared in Example 2 is as high as 97wt%, while the gel content of the uncross-linked Comparative Examples 1-3 is 0; the tensile strength of the copolymer prepared in Example 2 is significantly higher than that of the samples with similar composition prepared in Comparative Examples 1-3. With the formation of the cross-linked structure, the elongation at break of the material is lower than that of the uncross-linked Comparative Examples 1-3, but the tensile strength of the prepared copolymer is comparable to that of the traditional vulcanized cross-linked sample (Comparative Example 4), and the elongation at break is much higher than that of the traditional vulcanized cross-linked sample. All of these indicate that the reversible cross-linked chemical structure formed by the various components of the present invention can replace the traditional irreversible cross-linking method, and the elasticity and toughness of the material are significantly improved while maintaining the stability of the basic mechanical properties of the material.

[0098] In addition, from the comparative analysis of the results of Example 2, Example 2', Example 2" and Comparative Example 4, it can be seen that the present invention forms a reversible chemical bond between the acrylate copolymer macromolecules through the thermal reversible reaction between furan / maleimide, and the chemical bond can be dissociated by a reverse reaction at high temperature, so that the cross-linked acrylate copolymer is decrosslinked, giving the cross-linked polymer reproducibility, that is, the sample prepared in Example 2 can be repeatedly processed to obtain the sample of Example 2', and the sample of Example 2' is processed again to obtain the sample of Example 2"; at the same time, it can be seen from the data in Table 2 that the mechanical properties of the samples of Example 2' and Example 2" are basically unchanged compared with the sample of Example 2, which shows that the reversible crosslinking of the present invention can give the material multiple processability, and the performance of the material can still be maintained after processing. However, the traditional vulcanization crosslinked sample (Comparative Example 4) cannot be repeatedly processed once the material is formed because the crosslinked chemical bond is not reversible. It can be seen that the present invention can achieve green recycling of crosslinked rubber.

[0099] The FTIR test was conducted using Nicolet 6700 Fourier transform infrared spectrometer. The thermal reversibility of the DA reaction was observed by infrared spectroscopy. The results are as follows: Figure 2 In the six-membered ring produced by the DA reaction, the in-plane bending vibration of the ether bond COC will appear at 1177 cm -1 The variable temperature FTIR test can more clearly observe the process of DA bonding generation and breaking in the sample as the temperature changes. The reversibly cross-linked sample prepared in Example 2 was subjected to a variable temperature infrared spectrum test: the cross-linked sample was heated to 140°C for infrared data scanning, and the reverse DA reaction occurred. Figure 2 The center is 1177cm-1 The characteristic peak intensity of the COC bond in the six-membered ring introduced by the DA reaction at 140°C decreases with increasing temperature; when the decrosslinked sample is cooled to 40°C, the peak at 1177cm -1 The characteristic intensity of the COC bond of the six-membered ring at increases again, indicating that the DA reaction occurs. This indicates that the reversible process of DA reaction dissociation at elevated temperature and association at lowered temperature is successfully achieved in the synthesized acrylic rubber prepared by the present invention.

[0100] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A cross-linked acrylate copolymer, characterized in that: The copolymer comprises a structural unit A derived from acrylate, a structural unit B derived from ethylene, a structural unit C derived from furan-substituted acrylate, and a structural unit D derived from a coupling agent; Based on the total amount of the copolymer, the content of the structural unit A is 10-80 wt %, the content of the structural unit B is 15-82 wt %, the content of the structural unit C is 3-10 wt %, and the content of the structural unit D is 1-6 wt %.

2. The cross-linked acrylate copolymer according to claim 1, characterized in that The gel content of the copolymer is not less than 80 wt %. The infrared spectrum of the copolymer has a wavelength of 1177 cm -1 The characteristic peak of ether bond COC appears nearby.

3. The cross-linked acrylate copolymer according to claim 1 or 2, characterized in that: The elongation at break of the copolymer is not less than 180%.

4. The cross-linked acrylate copolymer according to any one of claims 1 to 3, characterized in that The furan-substituted acrylate is selected from and / or Preferably 5. The cross-linked acrylate copolymer according to any one of claims 1 to 4, characterized in that The coupling agent is selected from and / or Wherein R is an alkylene group of 1 to 10 carbon atoms.

6. A method for preparing a cross-linked acrylate copolymer, characterized in that: In the presence of an initiator, acrylate, furan-substituted acrylate and ethylene are polymerized, and after the reaction, the ethylene is discharged, and then a coupling agent is added to carry out a cross-linking reaction to obtain a cross-linked acrylate copolymer.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the furan-substituted acrylate to the acrylate is 1:9-3:8; And / or, preferably, the pressure of ethylene is 1-100 MPa.

8. The preparation method according to claim 6 or 7, characterized in that: The amount of the initiator is 0.01%-1wt% of the total mass of the acrylate and the furan-substituted acrylate; And / or, preferably, the polymerization reaction temperature is 0-100°C and the time is 0.1-12h.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The mass ratio of the coupling agent to the furan substituted acrylate is 0.1-0.5:1; And / or, preferably, the temperature of the cross-linking reaction is 40-80° C., and the time is 0.1-12 h.

10. Use of a cross-linked acrylate copolymer as a reinforced acrylate rubber material.

Citation Information

Patent Citations

  • Styrene copolymers with reversible cross bonds and preparation method of styrene copolymers

    CN107337748A

  • Preparation and restoration methods for thermally-reversible self-repairing polymeric material

    CN107973886A

  • Ethylene propylene rubber / polyethylene glycol copolymer and preparation method thereof

    CN109293929A

  • Propylene copolymer and preparation method and application thereof

    CN110669175A

  • Polypropylene resin with high melt index and high melt strength and preparation method thereof

    CN116462803A